Faktor-faktor yang Berhubungan dengan Kebiasaan Merokok pada Remaja Putra Kelas X dan XI di SMA Negeri 6 Pekanbaru - Rina Yulviana (Jurnal Kesehatan Komunitas, 2015)
Smoking is a habit that is difficult to stop, as well as a negative impact for the smoker and the people around him. Survey of World Health Organizatio (WHO), teen deaths in 2030 reached 10 million people per year. While in Indonesia, University of Indonesia Demographic surveys by as many as 427 948 people dead teenagers on average per year from a variety diseases caused by smoking, The purpose of this study was to determine the relationship factor allowance, dad smokers, and smokers with peers on adolescent smoking son in SMA 6 Pekanbaru. This study cross-sectional design with a quantitative approach. The study population was all students in classes X and XI SMA Negeri 6 Pekanbaru amounted to 390 people with a large sample of 131 people. This study using simple random sampling technique. Statistical tests using the chi square test. The results obtained from the 131 respondents, 63 people (48.1%) had a smoking habit, 38 people (44.2%) had high knowledge about cigarette with p value 1.6, 36 people (59%) related to the allowance p value = 0.03, 54 people (56.3%) related by father smokers with p value 0.04, 45 people (57.7%) related to peer smokers with p value 0.01. The conclusion of this study is the relationship between money pocket, dad smokers, and smokers with peer smoking habits in young men in the class X and XI SMA 6 Pekabaru.